Treatment of multiple sclerosis with rituximab: A multicentric Italian–Swiss experience. (October 2020) - Zecca, Chiara; Bovis, Francesca; Novi, Giovanni; Capobianco, Marco; Lanzillo, Roberta; Frau, Jessica; Repice, Anna Maria; Hakiki, Bahia; Realmuto, Sabrina; Bonavita, Simona; Curti, Erica; Brambilla, Laura; et al.
Background: Rituximab, an anti-CD20 monoclonal antibody leading to B lymphocyte depletion, is increasingly used as an off-label treatment option for multiple sclerosis (MS). Objective: To investigate the effectiveness and safety of rituximab in relapsing–remitting (RR) and progressive MS. Methods: This is a multicenter, retrospective study on consecutive MS patients treated off-label with rituximab in 22 Italian and 1 Swiss MS centers. Relapse rate, time to first relapse, Expanded Disability Status Scale (EDSS) progression, incidence of adverse events, and radiological outcomes from 2009 to 2019 were analyzed. Results: A total of 355/451 enrolled subjects had at least one follow-up visit and were included in the outcome analysis. Annualized relapse rate significantly decreases after rituximab initiation versus the pre-rituximab start year in RRMS (from 0.86 to 0.09, p < .0001) and in secondary-progressive (SP) MS (from 0.34 to 0.06, p < .0001) and had a slight decrease in primary-progressive (PP) MS patients (from 0.12 to 0.07, p = 0.45). After 3 years from rituximab start, the proportion of patients with a confirmed EDSS progression was 14.6% in the RRMS group, 24.7% in the SPMS group, and 41.5% in the PPMS group. No major safety concerns arose. Conclusion: Consistently with other observational studies, our data show effectiveness of rituximab in reducing disease activity in patients with MS.